Device for determining critical wind speed of stalk breaking to evaluate maize lodging resistance - Xue, Jun; Ming, Bo; Wang, Keru; Xie, Ruizhi; Hou, Peng; Li, Shaokun (International Journal of Agricultural and Biological Engineering, 2020)
The accurate evaluation of the lodging resistance of maize plants can provide a basis for the breeding of lodging-resistant cultivars and the regulation of cultivation measures. However, the traditional methods for evaluating maize lodging resistance in terms of plant morphology and stalk mechanical strength have certain limitations. The objective of this research was to develop a device for determining the critical wind speed of maize stalk breaking. The device used a centrifugal fan to supply airflow and was powered by a frequency conversion motor. The frequency converter adjusted the motor speed and thus adjusted the wind speed. The wind speed decreased first and then increased with increasing height above the outlet of the device, and maximum wind speed can reach 40 m/s. This device was convenient for transportation in the field, has a low cost, and can quickly, accurately, and objectively determine the lodging resistance. Field tests showed that the device ran stably for a long time. The coefficient of variation of three repeated measurements was between 1.5% and 4.8% for four maize cultivars. The new device can measure the critical wind speed of maize lodging and identify the lodging resistance for different maize cultivars, cultivation practices, and plant health conditions, and can thus overcome barriers to measuring the maize lodging resistance under natural wind conditions.Keywords: maize, stalk lodging, critical wind speed, turbofan, measuring device, wind pressureDOI: 10.25165/j.ijabe.20201305.6033Citation: Xue J, Ming B, Wang K R, Xie R Z, Hou P, Li S K. Device for determining critical wind speed of stalk breaking to evaluate maize lodging resistance. Int J Agric & Biol Eng, 2020; 13(5): 1–7.